Atividade inseticida e repelência de óleos essenciais de eucalyptus sobre Zabrotes Subfasciatus (BOHEMAN, 1833) E Sitophilus zeamais (MOTSCHULSKY, 1855) - Alves, Agripino Emanuel Oliveira (2021)
Storing food is a practice observed since the beginnings of production and agricultural exploitation, it is a fundamental strategy to ensure society's food for a certain period. Currently in agriculture, whether corporate or family, storage is used to ensure the quality of the product and trade. However, these stored and stored foods are targets of pests and insects that compromise production. Thus, measures to control and eliminate these pests are necessary, through various methods, whether with chemical or biological control. Therefore, this work aimed to analyze the bioinsecticide potential of essential oils extracted from Eucalyptus genotypes for the control of storage pests in the production of beans (Zabrotes Subfasciatus) and corn (Sitophilus zeamais), under laboratory conditions, using essential oils from 4 Eucalyptus genotypes (1249, 1250, 1277 and 0292). The oils were tested for repelling action and lethal concentrations for pest control. In the studies of mortality by contact of pest insects, 4 Eucalyptus genotypes were analyzed, with 3 different concentrations being for Z. subfasciatus (1%, 2%, 2.5%), and for Sitophilus zeamais (5%, 10%, 20%), plus one positive and one negative control, with 10 replicates in randomized blocks. For the free-choice repellent action studies on the pest insects Z. subfasciatus and S. zeamais, essential oils from 4 Eucalyptus genotypes were tested with 5 replications for each treatment, in a completely randomized block design. All tested oils showed repellent action on insects and were efficient in the mortality of insect pests Z. subfasciatus and S. zeamais.